Pengaruh Brand Awareness, Norma Subyektif, Keyakinan Label Halal Terhadap Brand Attitude Untuk Meningkatkan Minat Beli Ulang Ice Cream Magnum - maratush sholihah; Henny Welsa (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research is to know the positive influence of brand awareness toward brand attitude, subjective norm toward brand attitude, belief of label of halal to brand attitude, brand attitude toward buying interest, brand awareness to buying interest and belief of halal label to buy interest. The population is ice cream customers Magnum Muslim Students in Yogyakarta. Number of samples 100 respondents, sampling method purposive sampling and accidental sampling. Method of taking data using questioner. The analysis technique used is multiple linear regression equation with 5% significant level. The results showed: 1) brand awareness has a positive and significant effect on brand attitude of Magnum ice cream to Muslim Students in Yogyakarta; 2) subjective norms have positive and significant influence on brand attitude of ice cream Magnum at Muslim Student in Yogyakarta 3) belief of label of halal have positive and significant effect to brand attitude of ice cream Magnum to Muslim Student in Yogyakarta; 4) brand attitude has a positive and significant influence on the interest to buy Magnum ice cream to Muslim Students in Yogyakarta; 5) brand awareness has a positive and significant impact on the interest of Magnum ice cream buy back to Muslim Students in Yogyakarta; 6) the belief of the halal label has a negative and insignificant effect on the interest of Magnum ice cream buy back to Muslim StudentsKeywords : brand awareness, subjective norms, label beliefs halal, brand attitude, and buying interest